Empowering Informal Traders through Developmental Local Government: The Case of Polokwane Local Municipality - Selepe, Modupi (My University, 2025)
South Africa’s democratic dispensation brought hope and trust to oppressed black citizens, particularly the promise of economic emancipation and freedom, as highlighted in the ruling party’s manifestos and the Freedom Charter. However, post-democracy challenges such as unemployment, poverty, marginalisation, and lack of social security have led to an increasing number of informal traders operating within areas managed by local municipalities since the introduction of developmental local government. Consequently, informal trading has gained significant momentum and reshaped urban landscapes, both locally and globally. The South African Local Government Association (SALGA) introduced the concept of Developmental Local Government (DLG), mandating municipalities to collaborate with communities to promote economic development, including informal traders. This study aimed to develop an informal trader empowerment model/framework. The Dualist Theory of the informal economy was adopted, which posits that individuals participate in the informal economy due to socio-economic factors such as poverty, unemployment, and marginalisation. This theory was validated through findings indicating that participants engaged in informal trading for survival. A mixed-method research approach was utilised, with an anti-positivist/interpretivist paradigm guiding the study. The research focused on Polokwane’s informal traders and the Polokwane Local Municipality. Non-probability sampling techniques, including convenience and purposive sampling, were employed to collect data from a total of 70 participants—50 informal traders and 20 municipal officials. Data collection involved focus group interviews to address time constraints and Covid-19 restrictions, with Personal Protective Equipment (PPE) ensuring safety. Data analysis primarily involved thematic analysis, complemented by the Statistical Package for Social Sciences (SPSS) and Microsoft Excel for quantitative enumeration. Ethical standards were rigorously adhered to, ensuring anonymity, protection from harm, voluntary participation, and securing permission from gatekeepers.
PhD (Public Administration)
Department of Public and Development Administration
Keywords: UCTD; Informal - traders -- South Africa; Local - government -- South Africa